Christian Marriage, Money Scams, and Melanesian Social Imaginaries. Issue 2 (July 2014) - Cox, John; Macintyre, Martha
Abstract In this paper, we draw on fieldwork with middle‐class investors in 'fast money schemes' (Ponzi scams) to consider how Neo‐Pentecostal Christianity may be mediating social and economic change in Papua New Guinea, particularly in relation to gender equality. Ideas of companionate marriage and the cultivation of an affective self imply masculinities that are more sensitive and less domineering. As these images of fulfilled modernity flow out from Pentecostal churches into broader Papua New Guinean society, they corroborate Taylor's theory of how change occurs within the modern social imaginary.